Triangles, tricks and tics: Hyper-mentalizing in response to animated shapes in Tourette syndrome. (October 2015) - Eddy, Clare M.; Cavanna, Andrea E.
Abstract: Tourette syndrome (TS) can feature complex tics involving socially inappropriate behaviours. Adults with TS can also demonstrate differences to healthy controls when reasoning about mental states. This study investigated spontaneous mentalizing in TS. Twenty adults with TS and twenty healthy controls completed the animations task. Participants were asked to watch short ambiguous animations involving two triangles and describe what was happening. Some animations featured random movement of the triangles, while others depicted social interactions that were simple (e.g., dancing) or more complex (e.g., one triangle tricking the other). Measures were taken of executive functions, alexithymia and clinical symptoms. Individuals with TS responded similarly to controls when viewing animations featuring simple and complex interactions, demonstrating intact mentalizing ability. However, significant group differences were apparent for the random movement animations. TS was associated with a greater tendency to attribute mental states during this condition, and to describe random movements as motivated actions guided by the intentions of the triangles. There were no group differences for the alexithymia scale, but TS was associated with mild executive deficits. No relationships were apparent between animation responses and other measures. Our findings suggest that TS is associated with a propensity to adopt the intentional stance. Hyper-mentalizing in TS could be linked to both dopamine dysfunction and altered social behaviour, whereby amplified salience of social cues could contribute to the complex interplay between environmental context and tic expression. These observations may offer further insight into the potential effects of dopamine dysfunction on social cognition.